MODIFIKASI WARNA, TEKTUR DAN AROMA TEMPE SETELAH DIPROSES DENGAN KARBON DIOKSIDA SUPERKRITIK [The Modification of Color, Texture, and Aroma of Tempe Processed with Supercritical Carbon Dioxide] - Maria Erna Kustyawati; Filli Pratama; Daniel Saputra; Agus Wijaya (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
Supercritical carbon dioxide technology was a non thermal processing which might be applied on tempe to preserve its freshness. The aim of the research was to study the effect of supercritical CO2 on the color and texture of tempe, and to identify the aroma of tempe after processed with supercritical CO2. The experiment was carried out using CompletelyRandomized Block Design with three replications. The experimental factors were pressure treatmentat supercritic (Ps) and liquid (Pc), and treatment time (T) at T1, T2, T3, T4 of 5, 10, 15, and 20 minutes, respectively. The results showed that the treatment of pressures, time and their interactions significantly affected the color of ∆L*, ∆a*, ∆b*, ∆E*, but not significantly affected the textures.The best treatment was PcT1 producing the tempe with the value of ∆L*-2.13; ∆a*0.28; ∆b*0.97 dan ∆E*0.77. Several volatile aromas of tempe were extracted due to the supercritical CO2 treatment, but it also caused the formation of new volatile aroma compounds.